PEMANFAATAN IDEF0 UNTUK ANALISIS KINERJA SISTEM MANUFAKTUR (STUDI KASUS: THE ORDER HANDLING MANUFACTURING SYSTEMS) - Budiarto, Slamet (Jurnal Matematika Sains dan Teknologi, 2007)
The IDEF0 (Integration Definition Language 0) developed by Douglas T.Ross and SoftTech.Inc is a procedure for modeling functionality as part of the Air Force programmed on computer-aided-manufacturing which based on SADT (Structured Analisys and Design Technique). Wang and Smith (1988) suggested that IDEF0 could be combined with SSM. IDEF0 is used to analysis manufacture systems, in this case OHMS. Data from research (Budiarto, 2005) on Division of General Engineering at PT.PAL use OHMS further analyzed in this study. Data analysis shows that IDEF0 can be used to mapping activity system, both at the global as well as detail views, and performance indicators for each detail activities can be developed trough IDEF0. In addition IDEF0 can be used as a tool in providing recommendation of performance improvement of manufacturing systems.